Possible Lagged Impact of the Arctic Sea Ice in Barents–Kara Seas on June Precipitation in Eastern China - Yang, Huidi; Rao, Jian; Chen, Haishan (Frontiers in Earth Science, 2022)
Based on the Hadley Centre sea ice concentration, the ERA5 reanalysis, and three precipitation datasets, the possible lagged impact of the Kara-Barents sea ice on June rainfall across China is investigated. Using the singular value decomposition, it is revealed that the state of sea ice concentration in Kara-Barents Seas from November-December is closely related to regional precipitation in June, which is most evident across the Yangtze-Huai Rivers Valley and South China. Possible pathways from preceding Arctic sea ice concentration to June precipitation are examined and discussed. First, the sea ice concentration usually has a long memory, which exerts a long-lasting and lagged impact, although the sea ice anomaly amplitude gradually weakens from early winter to early summer. Second, an increase in Kara-Barents sea ice usually corresponds to a stronger stratospheric polar vortex in midwinter by suppressing extratropical wave activities, which is projected to the positive phase of northern annular mode (NAM). Strong vortex gradually recovers to its normal state and even weakens in spring, which corresponds to the negative NAM response from spring to early summer. Third, the stratospheric anomalies associated with the Kara-Barents sea ice variations propagate downward. Due to the out-of-phase relationship between the lower and upper stratospheric circulation anomalies after midwinter, westerly anomalies in midwinter are followed by easterlies anomalies in later months in the circumpolar region, consistent with the positive NAM response in midwinter, negative NAM response in spring, and a wave train-like response in early summer to Kara-Barents sea ice increase (and vice versa). The observed lagged impact of Kara-Barents sea ice on China rainfall in June is limitedly simulated in CMIP6 models.